2017
DOI: 10.1002/mp.12722
|View full text |Cite
|
Sign up to set email alerts
|

Development of depth encoding small animal PET detectors using dual‐ended readout of pixelated scintillator arrays with SiPMs

Abstract: Four high resolution depth encoding small animal PET detectors were developed using dual-ended readout of pixelated scintillator arrays with SiPMs. The performance results show that those detectors can be used to build a small animal PET scanner to simultaneously achieve uniform high spatial resolution and high sensitivity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
35
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 43 publications
(35 citation statements)
references
References 44 publications
0
35
0
Order By: Relevance
“…To achieve a high spatial resolution, detector modules composed of discrete small detector components are commonly utilized to increase the number of samples taken in the spatial domain (Cutler et al 1992, Stortz et al 2017. However, joints or gaps (dead areas) existing between the detector components and/or modules reduce the sensitivity and, in some cases, produce artifacts (Nagarkar et al 2004, Kuang et al 2018. Moreover, manufacturing detector modules with very small scintillator elements to enhance the spatial resolution would considerably add to the cost of the PET scanner.…”
Section: Introductionmentioning
confidence: 99%
“…To achieve a high spatial resolution, detector modules composed of discrete small detector components are commonly utilized to increase the number of samples taken in the spatial domain (Cutler et al 1992, Stortz et al 2017. However, joints or gaps (dead areas) existing between the detector components and/or modules reduce the sensitivity and, in some cases, produce artifacts (Nagarkar et al 2004, Kuang et al 2018. Moreover, manufacturing detector modules with very small scintillator elements to enhance the spatial resolution would considerably add to the cost of the PET scanner.…”
Section: Introductionmentioning
confidence: 99%
“…On a smaller scale, preclinical PET systems already achieve nearly perfect spatial resolution uniformity with DOI resolutions on the order of 1 − 2 mm using detector module configurations that would be impractical for human scanners (i.e., thin crystals, dualended readout, etc.) [36][37][38][39], but our CNN method may enable more cost-effective preclinical systems to be developed with similar DOI resolution. In addition, a recent study demonstrated how sub-2 mm DOI resolution can enable uniform spatial resolution on the order of 1 mm due to drastically reduced parallax error [40].…”
Section: Accepted Articlementioning
confidence: 99%
“…OSITRON Emission Tomography (PET) [1][2] is a noninvasive medical imaging technique used to evaluate the metabolism level, biochemical reaction, and functional activity of various organs quantitatively and dynamically. In the field of biomedicine, studies need to be completed on small animals before extrapolation toward the humans, which requires high-quality small animal PET systems [3] [4]. High demands on the performance of their readout electronics Manuscript include high resolution of position, time, and energy measurement, real-time signal processing ability, as well as compatibility for multiple working modes.…”
Section: Introductionmentioning
confidence: 99%